Christians in Kuwait: a challenge for political tolerance - Abu Sulaib, Faisal Mukhyat (Middle East policy, 2022)
The study presented here seeks to determine whether Kuwaiti Christians feel politically and socially integrated, isolated, or even threatened in Kuwait society, as well as to explore their political attitudes and primary social demands. At the same time, the study examines the attitudes and tolerance of Kuwaiti Muslims toward the Christian minority. To that end, two questionnaires were distributed to Christians and Muslims. The results suggest that Christians feel integrated into Kuwaiti society rather than isolated or persecuted. Other results suggest that they are also interested in participating in parliamentary elections and think they should have a quota of seats in the Kuwaiti parliament and a Christian minister in the government. The study also reveals that Kuwaiti Muslims harbor a high level of intolerance toward the Christian minority, which should be a red flag for Kuwaiti government and society.